Uji Maqashid Syariah Perbankan Syariah Di Indonesia - Mahmudatus Sa’diyah; Asep Gugun Gumilar; Edi Susilo (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study is to examine the performance of Islamic banking in Indonesia based on MSI (Maqashid Shariah Index). Combining the maqashid sharia Ibn Ashur and Abu Zaharah with the methodological concept developed by Sekaran (Mohammed et al., 2015). The three objectives of Maqashid Sharia: (1) Tahdhib al-Fard (Educating individuals); (2) Iqamah al-ʻAdl (establishing justice); and (3) Jalb al-Maslahah (Public Interest). Simple Additive Weighting (SAW) is used as a method for ranking the performance of Islamic banking based on the final results from MSI. The results showed 14 Islamic Commercial Banks (BUS) in 2011-2019, had an average IMS 0.1694. The IMS of five Islamic banks is below the average, namely BMS, Maybank, BTPNS, BAS, and BNTBS. IMS first rank is BPS index 0.2336, second rank is BVS index 0.2168, third rank is BSB index 0.2164, fourth rank is BCAS with index 0.2129, fifth rank is BMI with 0.183 index, sixth rank is BSM with an index of 0.1895, the seventh rank is BRIS with an index of 0.1904, the eighth is BNIS with an index of 0.1814, the ninth is BJBS 0.1759, the tenth is BMS 0.153, the eleventh is Maybank index 0.1289, the twelfth is BTPNS 0.1237 the thirteenth is BAS 0.0930, and the last fourteen is BNTBS with an index of 0.1289